To share or hide under performance pressure: the role of supervisor support in shaping subordinate knowledge management behaviors - Xu, Jia; Chen, Jingrong; Lan, Qisi; Zhao, Man (Frontiers in Psychology, 2025)
IntroductionWhile knowledge sharing is widely acknowledged as a critical driver of organizational learning and development, employees may engage in knowledge hiding—particularly under performance-related pressure. This behavior can impede organizational growth, underscoring the need to understand the boundary conditions that determine whether performance pressure leads to knowledge sharing or knowledge hiding. Grounded in conservation of resources theory, this study proposes a dual-path model that examines how perceived supervisor support moderates the effects of employee performance pressure on knowledge management behaviors.MethodsTwo studies were conducted to test the proposed model. Study 1 employed a scenario-based experimental design, while Study 2 used a multi-wave survey approach. Both methods assessed the interaction between performance pressure and perceived supervisor support in predicting knowledge sharing and hiding behaviors.ResultsFindings revealed two distinct paths. The enrichment path was supported: when employees perceived high levels of supervisor support, performance pressure positively influenced their knowledge sharing behavior. Conversely, the depletion path was also confirmed: when supervisor support was perceived as low, performance pressure significantly increased tendencies toward knowledge hiding.DiscussionThis study advances understanding of the nuanced relationship between performance pressure and knowledge management behaviors by identifying perceived supervisor support as a key boundary condition. The dual-path model offers theoretical insights into how resource dynamics influence employee responses to stress, with practical implications for fostering positive knowledge behaviors in high-pressure work environments.